The Importance of Taste for Food Demand and the Experienced Taste Effect of Healthy Labels – An Experiment on Potato Chips and Bread - Linda Thunström; Jonas Nordström (Lund University, School of Economics and Management, Department of Economics, 2014)
This paper quantitatively analyzes the importance of taste versus health in food demand, as well as the effect on consumers' experienced taste of the non-intrinsic value of healthy labels. Our analysis is based on taste experiments and Vickrey second price auctions on potato chips and bread. Our findings imply a large positive effect on demand for potato chips from higher taste scores: when consumers' experienced taste from potato chips improves by one unit, the average willingness-to-pay (WTP) for a 150 gram bag of chips increases by 25 euro cents. The estimated effect from taste on bread demand is smaller, but may be sizeable for subgroups of consumers. Our evidence suggests that demand for chips and bread is unaffected by nutrition – the effect of the healthy label on WTP is not statistically significant. Finally, we find that consumers' experienced taste of a food is unaffected by the food carrying a healthy label.
Keywords: D12; D83; Q18; 330; willingness-to-pay for food; revealed preferences; taste; non-intrinsic value; healthy label